Wood Supply from Family Forests of the United States: Biophysical, Social, and Economic Factors - Brett J Butler; Emma M Sass (Forest Science, 2023)
Wood products are an essential provisioning ecosystem service with US forests providing nearly one-fifth of global wood supply. As of 2018, an estimated 46% of the annual wood harvested came from corporate forests, 42% came from family forests, and the remainder came from other private, public, and Tribal forests. The supply of wood from corporate forests is well described by traditional economic models, but the supply from family forests is much less well understood. This article combines data from three components of the USDA Forest Service’s Forest Inventory and Analysis program—plots, landowner surveys, and mill surveys—with other data to model the wood supply from family forests in the United States. Results are summarized in terms of bivariate relationships and a logistic regression model. The model results show that basal area, stand origin, forest type, having timber as an ownership objective, the amount of annual income derived from their forestland, proximity to a mill, management advice, and region are significantly associated with family forest timber harvesting. The results should be useful for forest industry analysts and others interested in understanding the current and potential future supply of wood from family forests. Study Implications: Family forests provide an estimated 42% of the annual timber harvested in the United States. It is important to understand the factors affecting their harvesting behaviors to design effective policies and programs to ensure a continual supply and sustainable management of this critical resource. This article shows that timber harvesting by family forest owners is influenced by a combination of biophysical, social, and economic factors, including basal area, stand origin, forest type, having timber as an ownership objective, the amount of annual income derived from their forestland, proximity to a mill, management advice, and region. These results suggest that programs aimed at increasing the area covered by planted stands, the area covered by softwood stands, and the number of owners receiving forest management advice may be particularly influential in maintaining and increasing the amount of wood harvested from family forests.